Efektivitas Penerapan LKPD Berbasis Problem Based Learning terhadap Hasil Belajar Siswa Kelas X MIA pada Materi Hakikat Ilmu Kimia - Sari Novi Delpia; Muhammad Alim Marhadi; La Rudi (Jurusan Pendidikan Kimia FKIP Universitas Halu Oleo, Jl. HEA. Mokodompit Kampus Hijau Bumi Tridharma Andounohu Kendari, Gedung MIPA FKIP UHO Sulawesi Tenggara – Indonesia, 2023)
This study aims to determine the description of student learning outcomes with the application of problem-based learning LKPD in class X MIA on the subject of the nature of chemistry, determine the effectiveness of problem-based learning LKPD in class X MIA on the subject of the nature of chemistry and student responses to the application of problem-based learning LKPD on the subject of the nature of chemistry. The subjects in this study were X MIA class students consisting of 18 students with 2 male students and 16 female students. The design in this study used a One-group Pretest Posttest Design research design. Data collection techniques were carried out by giving research instruments in the form of pretest and posttest questions and student response questionnaires. The results of this study indicate that the average initial test is 35.56% and the final test is 84.17%, the application of PBL-based LKPD is very effective in improving the learning outcomes of students in class X MIA SMAN 1 Anggaberi which is indicated by the average Ngain of 0.75. The overall percentage of student responses to the use of problem-based learning-based LKPD is 81.2% or in the very good category